LAYANAN BIMBINGAN KELOMPOK OLEH GURU BK TENTANG PEMAHAMAN KARIR SISWA SMA NEGERI 5 PONTIANAK - Sumardi, Sumardi; Asrori, M.; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research contained a group of counseling services by the counseling teacher about career understanding to year -10 students of ?SMAN 5 Pontianak?. The problem in this research are the stages, efforts and obstacles about students? career understanding based on group counseling. Thos research aimed to describe the stages of formations, transitions, activities and terminations. The subject of this research was the tenth grade students with the total of 45 students. The technique and tools used in this research are indirect communication with questionnaire and emergency guides. Based on the result of data analysis each aspect was classified into good category in can be seen in the percentage xhich shown 92%. The stages, the activities, and the terminations of students? career understanding based on group counseling also classified into good category.Keywords: Group Counseling, Career, High School, Transition, Formation.